An Optimality Theoretic Account of Place and Voice Assimilation in Bushehri Dialects - Kambuziya, Aliyeh Kord-e Zafaranlu; Aryaei, Pegah; Khorshid, Sahar Bahrami (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This paper intends to illustrate an analysis about one of the Common Phonological Processes in some regional varieties of Bushehri: assimilation, in the framework of Optimality Theory (McCarthy 2008). Bushehr Province with an area of 23167 square kilometers is located in south Iran. Speakers in this province can be divided in two general branches: northern and southern branches. Speakers in northern branch speak a dialect like Luri. Speakers in southern branch speak dialects that are like what is common in Fars Province. One of the taxonomy of assimilation is related to the influence of the sound features on the process of assimilation. This type of classification of assimilation can be according to two major parameters, place and voice. In Bushehri dialects there is a place assimilation in acuteness and graveness features. Hyman (1975 :31) argues that both consonants and vowels differ in this acoustic property of graveness/ acuteness. In Bushehri variteis, the back round vowel [u] before [+acute] consonants changes to front unround vowel [i] that has [+acute] feature. Also in Bushehri dialects when voicless palatal [c] placed before a voiced consonant, or when voicless alveolar [s] placed before a voiced consonant, they take voice feature from the voiced consonant and change to their adjacent pair [z] and [Éˆ]. Assimilation between adjacent segments is driven by the family of agreement constraints: AGREE [F]. Ranking AGREE[x] above IDENT[x] guarantees assimilation, in the other word the final ranking is as follow: AGREE [x] >> IDENT [x].